2012
DOI: 10.18806/tesl.v29i2.1097
|View full text |Cite
|
Sign up to set email alerts
|

Cooperating Teachers’ Roles and Responsibilities in a MATESOL Practicum

Abstract: Responding to a gap in relevant literatures, this study explores cooperating teachers’ perceptions of their roles and responsibilities as contributors to the practicum experiences of preservice teachers of English as a second language who were pursuing a master’s degree. Research tools featured focus group and individual interviews with 11 cooperating teachers who were working with practicum students. Findings include a perceived lack of communication between cooperating teachers and practicum course instructo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
(31 reference statements)
2
13
0
Order By: Relevance
“…This means that the relationship between the cooperating teacher and the student teacher, as indicated in this study, is hierarchical rather than reciprocal, thereby limiting the student teacher's involvement in the ongoing process of constructing and reconstructing knowledge with the cooperating teacher. These findings support the view that cooperating teachers should be informed of their roles and responsibilities as well as the competences they need to develop for mentoring practicum students effectively (Farrell, 2007;Payant & Murphy, 2012;Richards & Crookes, 1988).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This means that the relationship between the cooperating teacher and the student teacher, as indicated in this study, is hierarchical rather than reciprocal, thereby limiting the student teacher's involvement in the ongoing process of constructing and reconstructing knowledge with the cooperating teacher. These findings support the view that cooperating teachers should be informed of their roles and responsibilities as well as the competences they need to develop for mentoring practicum students effectively (Farrell, 2007;Payant & Murphy, 2012;Richards & Crookes, 1988).…”
Section: Discussionsupporting
confidence: 73%
“…They found that supervision was brief and uncoordinated and the feedback student teachers received was mainly evaluative, directive, and focused on general rather than subject-specific pedagogy. In an investigation into the cooperating teachers' perceptions of their roles and responsibilities while mentoring practicum students in the context of a MATESOL program in the United States, Payant and Murphy (2012) found that cooperating teachers were not quite clear about their roles and responsibilities in mentoring practicum students due to the lack of communication between cooperating teachers and practicum course instructors. This made the cooperating teacher-practicum student relationship problematic.…”
Section: Challenges Of the Tesol Practicummentioning
confidence: 99%
“…Given the literature, this is not surprising. Farrell (), for example, argued that “cooperating teachers tend to be untrained to work with learner teachers” (p. 228), and Payant and Murphy () stated that “it is naïve for anyone involved in the practicum to assume that a competent language teacher will automatically be able to serve as an effective cooperating teacher” (p. 20). In light of the results of Kissau et al (), who underscored the positive outcome on the edTPA for candidates who worked with trained CTs, WLTD experts should consider training all WL CTs.…”
Section: Discussionmentioning
confidence: 99%
“…It was often described as a persistent “gulf between theory and practice” (Heining‐Boynton, , p. 41). In their respective studies, Farrell () and Payant and Murphy () emphasized the need for “constructive working relationships between all parties who contribute to practicum experiences (i.e., language‐learners, practicum students, practicum course instructors, and other cooperating teachers” (Payant & Murphy, , p. 2). Although not specifically addressing WLTD, Zeichner () also noted that “cooperating teachers and university instructors are often mutually ignorant of each other's work and the principles that underlie it” (p. 61), urging that steps be taken to decrease academic fragmentation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation